Development and Evaluation of a Low-Cost and Portable Standing Wave Experiment Kit to Enhance Physics Learning - Puttisanwimon, Supachoke; Rakkapao, Suttida; Prasitpong, Singha; Ouyphon, Pornpaween; Wuttiprom, Sura (Journal of Inclusive and Innovative Education, 2025)
This study focuses on the development, evaluation, and educational application of a low-cost, portable experimental device designed to demonstrate standing waves in a classroom setting. The aim was to create an affordable and effective tool that allows students to directly observe, manipulate, and measure wave phenomena, enhancing their understanding of wave physics. The device incorporates modern technologies such as electronic sensors, microcontrollers, and other components to generate and measure standing waves on a flexible string. It consists of three main sections: a distance measurement unit, a frequency generation module, and the testing unit with a pulley system. The research employed a mixed-methods approach, including expert evaluations from five physics specialists, experimental testing to assess the device’s accuracy, and student feedback. The results demonstrated that the device produces accurate, reproducible measurements, with an average deviation of 0.89% when compared to theoretical predictions of wave speed. Expert evaluations rated the device highly in terms of its physical design, functionality, ease of use, and educational value. Furthermore, students reported a high level of satisfaction, highlighting the device’s ability to foster engagement and deepen their understanding of standing waves. This research contributes to the integration of affordable, technology-driven tools in science education, offering a practical solution for teaching complex concepts in physics. The findings suggest that such devices can enhance the learning experience by promoting active, hands-on experimentation, making physics more accessible and engaging for students. The study has implications for future developments in educational tools and methods in physics teaching.